Faktor-Faktor Yang Mempengaruhi Hasil Tangkapan Ikan Kembung (Rastrelliger SPP) di Perairan Selat Makassar - Syatir Suaib; Bambang Semedi; Paharuddin Paharuddin; A. Imran Anshari (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
This study aims to determine the factors that affect the catch of mackerel in the potential zone of fishing grounds in the Makassar Strait, namely; oceanography sea surface temperature, salinity, current velocity, depth and sea surface chlorophyll content on the catch of mackerel in the potential zone of fishing grounds in the Makassar Strait. The research method used is the survey method, which directly follows the fishing operation. The number of observations was 38 times. Data were analyzed with histogram graphs and also analyzed with multiple linear regression. The results of this study showed that mackerel were generally caught in waters with temperatures between280Cand290C; salinities of 30 ppt and 31 ppt; water depths of about 50 m and 60 m; current speeds of about 0.09 m/s and 0.12 m/s; and chlorophyll-a content of about 1.80 mg/m3 and 2.20 mg/m3. This study has explained that chlorophyll-a content is the dominant factor in relation to mackerel catch.